STATUS GIZI KAITANNYA DENGAN DISLIPIDEMIA PADA PRALANSIA DAN LANSIA - Dainy, Nunung Cipta; Kusharto, Clara M; Madanijah, Siti; Nasrun, Martina Wiwie Setiawan (Jurnal Gizi dan Pangan, 2016)
The objective of this study was to analyze the association of nutritional status measured by Body Mass Index (BMI) and Mini Nutritional Assessment (MNA) with lipid profile in pre-elderly and elderly. The study design was cross sectional involving 116 subjects in Poslansia Dahlia Senja, Depok City. Data were collected in September 2014 consisted of weight, height, arm circumference, calf circumference, and blood samples for lipid profile analysis. Blood analysis were conducted at Health Laboratory of Bogor City. The results showed that 61.1% pre-erderly and 54.5% elderly had BMI with category overweight and obese, while nutritional status measured by MNA were 62.7% pre elderly and 70.2% elderly had good nutritional status. There were 54.2% pre-elderly and 63.1% elderly people had dyslipidemia. Statistical analysis with correlation test showed there was significant correlation between BMI with triglycerides (r=0.201; p<0.05) and MNA with total cholesterol (r=0.264; p<0.05).